2008
DOI: 10.1177/0731684408091703
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Properties of Epoxy Resin Modified with Polyurethane

Abstract: Epoxy resin was modified with polyurethane having different isocyanate index. Impact strength, tensile strength, elongation at break and flexural strength were estimated as functions of polyurethane content and isocyanate index. Hardness, linear expansion coefficient and the deflection temperature under load were estimated for selected compositions. Infrared spectroscopy was carried out for unmodified epoxy resin and compositions with improved mechanical properties. Maximum improvement in the fracture toughnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 29 publications
(34 reference statements)
2
54
0
1
Order By: Relevance
“…24 The largest improvement in the fracture toughness was achieved with the PUR having the highest isocyanate content. The infrared spectra have indicated that the excess of isocyanate groups has produced grafting reactions between the modifier and the epoxy matrix, which explained the observed toughening effect.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…24 The largest improvement in the fracture toughness was achieved with the PUR having the highest isocyanate content. The infrared spectra have indicated that the excess of isocyanate groups has produced grafting reactions between the modifier and the epoxy matrix, which explained the observed toughening effect.…”
Section: Introductionmentioning
confidence: 83%
“…[11][12][13][14][15] Epoxy resin's properties have also been improved by using nanoparticles [16][17][18][19][20] as well as other cross-linkable polymers to form full-or semi-interpenetrating polymer networks. [21][22][23][24][25][26][27][28][29] Yilmazer and co-workers 16 have used unmodified montmorillonite (Cloisite Na + ) and organically modified Cloisite 30B as reinforcing agents for diglycidyl ether of bisphenol-A (DGEBA), Their results have shown an increase in the glass transition temperature (Tg) by more than 10°C with the addition of 9 wt% of a modified montmorillonite (MMT). The addition of 0.5 and 1 wt% of Cloisite 30B resulted in a maximum improvement in the impact strength of DGEBA.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the effect of isocyanate index of TDI-based PUR on the mechanical and thermal properties of diglycidyl ether of bisphenol A cured with triethylenetetramine was investigated, 11 and the positive effect of the reactive groups was confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In this respect, polyur-ethanes (PURs) proved to be successful, mainly due to their high flexibility and versatile structure. 18 PUR/EP grafted IPN with combined advantages of both the polymers were first reported by Frisch et al 6 It was demonstrated that PUR can be linked to EP through physical entanglements and chemical bonding to form graft IPN.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of tensile properties indicates that the polyurethane prepolymer terminated with hydroxyl groups and GO have the synergistic effect on improving tensile properties of neat EP. On one hand, the introduction of polyurethane prepolymer terminated with hydroxyl groups provides additional free volume, leading to more facilitated segmental movements 13) . On the other hand, the wrinkled topology at the nanoscale of GO results in an enhanced mechanical interlocking with the polymer chains, while the abundant oxygen-containing groups on GO s basal plane and edges may form covalent bonds with polymer matrix 14) .…”
Section: Tensile Propertiesmentioning
confidence: 99%